Assessment of the Physicochemical Parameters and the General Wellbeing of Oreochromis niloticus in Dadin Kowa Reservoir, Gombe State (Journal of Environmental Bioremediation and Toxicology, 2023)
The maximum sustainable yield of aquatic biota of a reservoir is maintained by periodic monitoring of its water quality and the ecological conditions. Physicochemical parameters and the general wellbeing of Oreochromis niloticus in Dadin Kowa reservoir were investigated. Water samples were collected from the three sampling stations (upper reaches, lower reaches and water midways) on biweekly basis for physicochemical analysis. Air temperature, water temperature, pH, transparency, electric conductivity, Dissolve Oxygen (DO), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Phosphates, nitrate were measured and monitored.  A total of 240 (120 male and 120 females) O. niloticus samples were obtained fortnightly for the period of 6 months (March – August, 2019) from Dadin kowa dam. Weight-length relationship and fish condition factor were determined. Negative allometric growth pattern was observed in both sexes of O. niloticus (b-values 1). The physicochemical parameters of the reservoir varied with months, and stations which may be due to change in weather cycle during the study period that occurs in the environment. Anthropogenic activities such as farming and cattle rearing, washing and fishing that are taking place around the reservoir had some impact on the water quality of the reservoir, especially during the rainy season which in turn may stress the life of fishes and thus reduce the degree of their wellbeing and thus, slowed the rate of growth. Despite the fact that this research found that the reservoir is fit to support the life of Oreochromis niloticus, there is need to check the physicochemical parameters and condition factor of the reservoir regularly for over a long period of time and across different seasons of the year, so as to ascertain the health status of the reservoir.
Keywords: Oreochromis niloticus; Physicochemical parameters; Weight; Condition factor; Dadin Kowa reservoir